The Effect of Loop Inclination on Natural Circulation Mass Flow Rate and Heat Removal Inside Rectangular Passive Cooling Loop - Budiyanto, N. R.; Deendarlianto, D; Yuliaji, D.; Oktaviandi, R.; Raharjo, E. P. A.; Mariyadi, S. A.; Pamungkas, A. E.; Setiawan, P. H.; Budiman, A. A.; Juarsa, M. (Atom Indonesia, 2025)
The use of passive cooling systems as a reactor safety measure has become a key approach to preventing future incidents similar to the Fukushima Daiichi NPP accident. These systems operate based on natural circulation, a process driven by temperature differences and elevation between the heat source and heat sink. Key design factors, such as the inclination angle of the rectangular loop, significantly influence this circulation. This study aims to investigate the effects of different inclination angles of the rectangular loop and variations in the initial water temperature in the Water Heating Tank (WHT) on the flow rate and heat removal capability. The research was conducted experimentally using a natural circulation rectangular loop facility, FASSIP-04 Ver.0, which has an inner diameter of 26.64 mm, a rectangular loop height of 2280 mm, and a width of 780 mm. The experimental variations were achieved by adjusting the water temperature inside the WHT to 50°C, 70°C, and 90°C. Meanwhile, the inclination angle of the loop was set to 30°, 60°, and 90° mass flow rate and heat removal capability was influenced by both the loop inclination angle and the water temperature in the WHT. The highest values were observed at a 90° inclination angle and a set temperature of 90°C, with a mass flow rate of 0.0241 kg/s, and heat removal rates of qH = 0.791 kW, qC = 0.489 kW. The resulting buoyancy force was stronger under these conditions, leading to greater heat removal through natural circulation compared to free convection, thereby increasing both mass flow rate and heat removal efficiency.